Validation of the Oxford WebQ Online 24-hour dietary questionnaire using biomarkers - Greenwood,DC; Hardie,LJ; Frost,GS; Alwan,NA; Bradbury,KE; Carter,M; Elliott,P; Evans,CEL; Ford,HE; Hancock,N; Key,TJ; Liu,B; et al. (American Journal of Epidemiology, 2019)
Oxford WebQ is an online dietary questionnaire covering 24 hours, appropriate for repeated administration in large-scale prospective studies including UK Biobank and the Million Women Study. We compared performance of the Oxford WebQ and a traditional interviewer-administered multi-pass 24-hour recall against biomarkers for protein, potassium and total sugar intake, and total energy expenditure estimated by accelerometry. 160 participants were recruited between 2014 and 2016 in London, UK, and measured at 3 non-consecutive time-points. The measurement error model simultaneously compared all 3 methods. Attenuation factors for protein, potassium, sugars and total energy intake estimated by the mean of 2 Oxford WebQs were 0.37, 0.42, 0.45, and 0.31 respectively, with performance improving incrementally for the mean of more measures. Correlation between the mean of 2 Oxford WebQs and estimated true intakes, reflecting attenuation when intake is categorised or ranked, was 0.47, 0.39, 0.40, and 0.38 respectively, also improving with repeated administration. These were similar to the more administratively burdensome interviewer-based recall. Using objective biomarkers as the standard, Oxford WebQ performs well across key nutrients in comparison with more administratively burdensome interviewer-based 24-hour recalls. Attenuation improves when the average is taken over repeated administration, reducing measurement error bias in assessment of diet-disease associations.